DEVELOPING PROJECT-BASED INSTRUCTIONAL MATERIALS WITH CHARACTER INSERTION ACCORDING TO CURRICULUM 2013 FOR GRADE SEVEN OF JUNIOR HIGH SCHOOL - ., NI KADEK ARIASIH; ., DR. LUH PUTU ARTINI, M.A.; ., DR. NI MADE RATMININGSIH, M.A. (Jurnal Pendidikan Bahasa Inggris Indonesia, 2016)
Penelitian ini bertujuan untuk mengembangkan materi pembelajaran untuk mengajar Bahasa Inggris menggunakan pembelajaran berbasis proyek berdasarkan kurikulum 2013 untuk siswa kelas tujuh dan mendeskripsikan bagimana materi pembelajaran bebasis proyek berpeluang untuk mengirtasikan nilai-nilai karakter. Penelitian ini menggunakan desain pengembangan oleh Sugiyono (2011), dan dilaksanakan di SMP Negeri 1 Singaraja, dimana dua guru Bahasa Inggris dan satu dosen dari Universitas Pendidikan Ganesha dipilih untuk menjadi penguji ahli. Data didapatkan dengan cara observasi, wawancara, penyebaran mengisi kuisioner, dan studi dokumen, dan dianalisis secara deskriptif. Hasil penelitian menunjukkan bahwa terdapat 6 kompetensi dasar yang dikembangkan menjadi 8 proyek dalam produk yang dikembangkan.. Sementara itu, ada 10 karakter yang dimasukkan ke dalam proyek yang dilatih untuk dimiliki oleh siswa melalui aktifitas dalam pengerjaan proyek. Mengenai kualitas produk, ditemukan bahwa nilai rerata produk dari uji ahli sebesar 4.54, melebihi skor interval 4.05. Temuan ini mengindikasikan bahwa produk termasuk materi yang sangat baik dan materi yang dikembangkan telah secara jelas merepresentasikan apa yang disebutkan dalam teori pembelajaran berbasis proyek dan harapan dari Kurikulum 2013. Kata Kunci : Kata-kata Kunci: Kurikulum 2013, materi pembelajaran, Pembelajaran Berbasis Proyek, pendidikan karakter This study aimed at: a) developing materials for teaching English using Project-Based Learning according to Curriculum 2013 for grade seven of junior high school, b) describing how the characters values were inserted into Project-Based Learning according to Curriculum 2013 for grade seven of junior high school, and 3) describing the quality of the developed materials. The study employed research and development design proposed by Sugiyono (2011) and was conducted in SMP Negeri 1 Singaraja, where two English teachers were selected as expert judges. Furthermore, one lecturer from Ganesha University of Education was also selected as expert judge to judge the quality of product being developed. The data were collected by means of observation, interview, administering questionnaire, and document study, and were analyzed descriptively. The results of the study showed that there were six basic competences in seventh grade which were developed into 8 different projects as a product of recent research. Meanwhile, there were ten character values that were smoothly practiced and inserted into project activities. Moreover, regarding the quality of the product, the findings showed that the mean score of the developed materials was 4.54, exceeding the interval score of 4.05 ( ). This indicates that the developed material was categorized as excellent material and the product had represented what was suggested by the theory proposed by Thomas which was used as a grand theory in recent study. Thus, it can be concluded that the developed materials are applicable to the implementation of Curriculum 2013.keyword : Curriculum 2013, instructional material, Project-Based Learning, characters values